Maternal phthalates exposure promotes neural stem cell differentiation into phagocytic astrocytes and synapse engulfment via IRE1α/XBP1s pathway - Fengzhen Cui; Shiyu Deng; Yan Fu; Tongtong Xu; Shuangshuang Bao; Siyi Wang; Yahang Lin; Xianghui Wang; Faming Zhao; Tingting Zhang; Shunqing Xu; Zhijun Zhang; et al. (Cell Reports)
Summary: Humans are widely exposed to phthalates, a common chemical plasticizer. Previous cohort studies have revealed that maternal exposure to monobutyl phthalate (MBP), a key metabolite of phthalates, is associated with neurodevelopmental defects. However, the molecular mechanism remains unclear. Here, we demonstrate that maternal exposure to MBP enhances neural stem cell (NSC) differentiation into astrocytes with highly expressed C3 and LCN2 in mouse offspring, resulting in increased synapse phagocytosis and cognitive dysfunction. Mechanistically, we find that MBP exposure activates the IRE1α/XBP1s (spliced XBP1) stress response pathway, which regulates key genes involved in astrocyte differentiation (SOX9 and ATF3) and reactivity (C3 and LCN2). Conditional knockout or pharmacological inhibition of IRE1α markedly inhibits NSC differentiation into astrocytes and astrocyte reactivity, attenuates synapse phagocytosis, and improves cognitive function. This phenotype is further recapitulated in a human brain organoid model. Together, these findings unveil the molecular mechanism underlying the neurodevelopmental deficits caused by a widespread environmental pollutant.